Love is all you need [videorecording (DVD)] = Den skaldede frisør - Bier, Susanne, 1960-; Brosnan, Pierce; Bodnia, Kim, 1965-; Dyrholm, Trine, 1972-; Steen, Paprika, 1964-; Egelind, Molly Blixt (Sony Pictures Home Entertainment, 2013)
A hairdresser completes her cancer treatment, walks into her home to celebrate with her family, and is met with a even bigger surprise.